Lipid profile and anthropometry indices of franchised fast-food consumers in South Western states in Nigeria: Nutritional Status of consumer of franchised fast food in south western states in Nigeria - Uthman-Akinhanmi, Yewande; Ademiluyi, Dare; Oyewumi, Boluwatife; Akinola, Oyetunji; Ilo, Jumoke; Eviano, Okolosi Joel; Adenike, Akinyemi (World Nutrition Journal, 2024)
Background: Franchised fast foods are known for their unique tastes as it contains a number of spices that makes it delicious. Daily busy schedules have made consumption of franchised fast foods (FFFs) an easy option and control of our food choices even at home. Objective: This research investigated the lipid profile and anthropometric indices of consumers of franchised fast foods (FFFs) in South-Western States in Nigeria. Methods: This was a cross-sectional study in South-West Nigeria and comprised three states: Lagos, Oyo, and Ogun. 300 respondents were recruited from ten (10) purposively selected fast-food outlets in Ikeja, Abeokuta and Ibadan cities, Nigeria. Standardized method for assessing plasma lipid profile was used. A well-structured and pretested questionnaire was used for the survey. The statistical analysis was done using 95% confidence interval and an error percentage of 5%. Results: The major consumers of FFFs are single, younger adults, educated, and relatively high-income earners. Majority of male (39% and 23%) and females (33% and 41%) have excellent and good health status respectively. Significant association was observed between BMI and HDL-C (p=0.009) of male, and Significant differences existed among the BMI and all lipid profiles of female respondents (p<0.050). Conclusion: The study conclude that both genders are at risk of age-related NCDs in the future due to inadequate physical activity and dependence on FFFs. The consumption of FFFs is common among young people, high-income earners and educated people.